Analysis of Online Learning System Needs Based on MOOCs - Fitri Masito; Eko Risdianto; I Gusti Agung Ayu Mas Oka; Yanti Daryanti; Irwan Fathurrochman (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze the needs of an online learning system based on MOOCs at Poltekbang Palembang. This type of research is survey research which can later become the basis for further development research. The research instrument used was a needs analysis questionnaire with 21 questions given to 115 respondents who were students of the Palembang Poltekbang. In this study, data analysis used descriptive statistics. Based on the results of the data obtained, it can be concluded that currently, students need an online learning system based on MOOCs. It is based on the data obtained from all statements regarding the needs of Palembang Poltekbang students for effective online learning. Almost all of them were answered, with the most significant percentage being in the answer choices strongly agree and agree. Students need the points offered in each statement that they fill out on the needs questionnaire sheet. The Va value of 3.4339 was also obtained from the data obtained, which entered the valid category. While the reliability value obtained is 0.91, and the value is greater than r table for df = 113, which is 0.1832 because rcountrtable, then it is included in the reliable category.